Central Venous Catheterization: Are We Using Ultrasound Guidance?. (9th October 2015) - Adhikari, Srikar; Theodoro, Daniel; Raio, Christopher; Nelson, Mathew; Lyon, Matthew; Leech, Stephen; Akhtar, Saadia; Stolz, Uwe
Abstract : Objectives: To assess the self‐reported frequency of use of ultrasound guidance for central venous catheterization by emergency medicine (EM) residents, describe residents' perceptions regarding the use of ultrasound guidance, and identify barriers to the use of ultrasound guidance. Methods: A longitudinal cross‐sectional study was conducted at 5 academic institutions. A questionnaire on the use of ultrasound guidance for central venous catheterization was initially administered to EM residents in 2007. The same questionnaire was distributed again in the 5 EM residency programs in 2013. Results: In 2007 and 2013, 147 and 131 residents completed questionnaires, respectively. A significant increase in the use of ultrasound guidance for central venous catheterization was reported in 2013 compared to 2007 ( P < .001). In 2007, 53% (95% confidence interval, 44%–61%) of residents reported that they were initially trained in central venous catheterization using ultrasound guidance compared to 96% (95% confidence interval, 92%–99%) in 2013 ( P < .0001). In 2007, more residents thought that faculty were insufficiently adopting ultrasound (42% versus 9%), and there was a lack of ultrasound teaching during residency training (14% versus 5%) compared to 2013. Conclusions: The use of self‐reported ultrasound guidance for central venous catheterization significantly increased from 2007 to 2013 at academic institutions. Most residents were aware of the benefits of using ultrasound guidance. Although faculty adoption of ultrasound for central venous catheterization remains a barrier, it has decreased.